Average Error: 1.0 → 0.1
Time: 25.5s
Precision: 64
$\cosh \left(x + 1\right) - \cos x$
$\sqrt[3]{\cosh \left(x + 1\right) - \cos x} \cdot \left(\sqrt[3]{\cosh \left(x + 1\right) - \cos x} \cdot \sqrt[3]{\cosh \left(x + 1\right) - \cos x}\right)$
\cosh \left(x + 1\right) - \cos x
\sqrt[3]{\cosh \left(x + 1\right) - \cos x} \cdot \left(\sqrt[3]{\cosh \left(x + 1\right) - \cos x} \cdot \sqrt[3]{\cosh \left(x + 1\right) - \cos x}\right)
double f(double x) {
double r13267259 = x;
double r13267260 = 1.0;
double r13267261 = r13267259 + r13267260;
double r13267262 = cosh(r13267261);
double r13267263 = cos(r13267259);
double r13267264 = r13267262 - r13267263;
return r13267264;
}


double f(double x) {
double r13267265 = x;
double r13267266 = 1.0;
double r13267267 = r13267265 + r13267266;
double r13267268 = cosh(r13267267);
double r13267269 = cos(r13267265);
double r13267270 = r13267268 - r13267269;
double r13267271 = cbrt(r13267270);
double r13267272 = r13267271 * r13267271;
double r13267273 = r13267271 * r13267272;
return r13267273;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 1.0

$\cosh \left(x + 1\right) - \cos x$
2. Using strategy rm
$\leadsto \color{blue}{\left(\sqrt[3]{\cosh \left(x + 1\right) - \cos x} \cdot \sqrt[3]{\cosh \left(x + 1\right) - \cos x}\right) \cdot \sqrt[3]{\cosh \left(x + 1\right) - \cos x}}$
$\leadsto \sqrt[3]{\cosh \left(x + 1\right) - \cos x} \cdot \left(\sqrt[3]{\cosh \left(x + 1\right) - \cos x} \cdot \sqrt[3]{\cosh \left(x + 1\right) - \cos x}\right)$
herbie shell --seed 1